2018
DOI: 10.1016/j.eurpsy.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in mental health professionals: A systematic review and meta-analysis of prevalence and determinants

Abstract: This study aimed to estimate the level of burnout in mental health professionals and to identify specific determinants of burnout in this population. A systematic search of MEDLINE/PubMed, PsychINFO/Ovid, Embase, CINAHL/EBSCO and Web of Science was conducted for original research published between 1997 and 2017. Sixty-two studies were identified as meeting the study criteria for the systematic review. Data on the means, standard deviations, and prevalence of the dimensions of burnout were extracted from 33 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
247
7
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(311 citation statements)
references
References 99 publications
13
247
7
11
Order By: Relevance
“…The EE burnout of working as doctor and nurse, native‐born and permanent staffs, frequent night shift, and less family or friend parties were more sever in comparison. Connor et al reported that a sense of professional autonomy and being fairly treated were connected to EE. Chico‐Barba et al also found a significant association between night shift and EE.…”
Section: Discussioncontrasting
confidence: 50%
“…The EE burnout of working as doctor and nurse, native‐born and permanent staffs, frequent night shift, and less family or friend parties were more sever in comparison. Connor et al reported that a sense of professional autonomy and being fairly treated were connected to EE. Chico‐Barba et al also found a significant association between night shift and EE.…”
Section: Discussioncontrasting
confidence: 50%
“…The job expectations of a radiation therapist, working practices and extent to which opportunities for professional development exist can be expected to differ across geographical regions. Furthermore, factors that vary between workplaces such as access to clinical supervision, workload, relationships at work, role clarity, professional autonomy or sense of being fairly treated may influence the heterogeneity of burnout, likewise to what was observed in other studies pertaining to different health professionals (Cañadas‐De la Fuente et al, ; O'Connor et al, ; Trufelli et al, ).…”
Section: Discussionmentioning
confidence: 58%
“…In what concerns the levels of burnout observed, the estimated pooled prevalence of emotional exhaustion, depersonalisation and personal accomplishment for radiation therapists were 38.7%, 21.5% and 28%, respectively, which must be interpreted with caution due to the small number of studies available. To allow a comparison with other studies, a meta-analysis of burnout in mental health professionals reported the corresponding proportions to be 40% for EE, 22% for DP and 19% for PA (O'Connor, Muller Neff, & Pitman, 2018), whereas a meta-analysis of burnout in cancer professionals reported 36% for EE, 34% for DP and 25% for PA (Trufelli et al, 2008). A meta-analysis of health professionals working in palliative care reported 17.5% for EE, 6.5% for DP and 19.5% for PA (Parola, Coelho, Cardoso, Sandgren, & Apóstolo, 2017), and a meta-analysis of burnout in oncology nursing reported 30% for EE, 35% for DP and 35% for PA (Cañadas-De la Fuente et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The study did not directly measure burnout in mental health providers; however, other studies have shown that 40% of mental health providers suffer from burnout (O'Connor et al, 2018), indicating that the trends seen in residents may be generalizable to mental health providers.…”
Section: Burnout and Biasmentioning
confidence: 93%